International Commercial Arbitration Put to the Test in the Commonwealth - Butler, Petra (Victoria University of Wellington Law Review, 2020)
The article discusses the Commonwealth Study on international commercial arbitration conducted in 2019. The importance of the availability of international commercial arbitration as a dispute resolution mechanism lies in the link between trade and the accessibility of a dispute resolution mechanism that reflects the needs of cross-border trade. Given that the Commonwealth has a unique legal and trade ecosystem the Study provides a rare opportunity to consider what a best practice modern international commercial arbitration framework should look like to encourage cross-border trade.